United Nations access challenges and non-state armed groups in conflict situations: The need for legal reform - Makhlouf, Omneya (AUC Knowledge Fountain, 2016)
During situations of armed conflict, United Nations (UN) agencies have been consistently faced with challenges to access vulnerable populations in order to fulfill their humanitarian mandates. This is particularly true in countries such as Yemen, Libya, and Ukraine who have faced prolonged conflict situations from as early as 2010. During these conflicts, UN agencies have been frequently unable to enter areas that are controlled by non-state armed groups. There are several legitimate reasons for these access challenges, one of which includes the inadequate legal framework that governs non-state armed groups. This is not to neglect the operational and executive ineffectiveness of the UN or the political dynamics that shape these conflicts. In fact, this paper argues that these aspects complement the insufficiencies that are witnessed within the international legal system. The ineffectiveness of the UN, which is ultimately driven by the political interests of states, have not only been part and parcel to the genesis and influx of non-state armed groups in the respective countries, but have also played a major role in maintaining the legal positioning of non-state armed groups as a byproduct of the international system rather than main actors. The paper maintains that non-state armed groups have become significant players in international relations due to their increase in regional power and ability to affect politics. With this reality, the current legal framework that governs non-state armed groups has been proven to be an insufficient mechanism of enabling the interaction between UN agencies and non-state armed groups. In an attempt to ease such an interaction, the paper proposes some legal reforms, which are based on findings that prove the inconsistencies of that legal framework. It also offers policy suggestions for operational reforms within the UN system to facilitate the efficient implementation of the legal reforms.